Trends of Islamic State of Iraq and Syria (ISIS) Acts of Terrorism Targeting the Shia Community - Wibowo, Prihandono; Dwi Hapsari, Renitha (KnE Social Sciences, 2022)
The Islamic State of Iraq and Syria (ISIS) has consistently attacked Shia communities, and buildings belonging to these communities, both in the Middle East and outside the region. This paper tries to explain the logic and justification used by ISIS in making the Shia community a target of terrorism. To answer this question, this paper uses the concept of religious terrorism and framing through the phenomenon of terrorism. By analyzing various ISIS documents related to Shia issues, this paper describes the framing developed by ISIS for attacking Shia groups. This paper finds that ISIS creates anti-Shia framing by combining theological problems, Middle East socio-political conditions, and end-time eschatological beliefs. From a theological point of view, ISIS believes that the Shia are an ‘apostate’ group that deserves to be fought. In the socio-political context, ISIS considers that Shia groups work with foreign countries to fight Islam. In terms of eschatological beliefs, ISIS considers Shiites to support the Dajjal in the end times that must be fought. On the other hand, ISIS claims that its group is a legitimate caliphate and defender of Islamic teachings. These things shape ISIS’ hostile attitude towards Shia groups. Keywords: Shia, ISIS, terrorism, framing